2017
DOI: 10.1111/pai.12720
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin‐reactive T cells in Italian children from preventCD cohort at high risk of celiac disease

Abstract: T cells reactive to gliadin can be detected in the intestine of children at high risk of developing CD, in some cases also in the presence of a normal mucosa and negative CD-associated antibodies. Furthermore, children at a very early stage of CD recognize the same gliadin epitopes that are active in adult CD patients. Tissue transglutaminase strongly enhances gluten T-cell immunogenicity in early CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In this study, the ability of heterozygous DR5/DR7 B-LCLs, from both celiacs and healthy controls, to present gliadin peptides to CD4 + T cells was compared to DR1/DR3 B-LCLs, in the same experimental conditions. The antigen presenting function of DR5/DR7 and DR1/DR3 B-LCLs was assessed by dosing the IFN-γ production in a T cell line generated from small intestinal mucosa of a DR5/DR7 patient previously described 6 and highly reactive to the immunodominant gliadin peptide (DQ2.5-glia-α1,2, QLQPFPQPELPYPQPQP). DR5/DR7 B-LCL#23 (Table 1 ), carrying the DQ2.5 genes in trans configuration, displayed overlapping ability to stimulate cognate TCL with respect to DR1/DR3 B-LCL#5, as shown in dose curve response to DQ2.5-glia-α1,2 peptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the ability of heterozygous DR5/DR7 B-LCLs, from both celiacs and healthy controls, to present gliadin peptides to CD4 + T cells was compared to DR1/DR3 B-LCLs, in the same experimental conditions. The antigen presenting function of DR5/DR7 and DR1/DR3 B-LCLs was assessed by dosing the IFN-γ production in a T cell line generated from small intestinal mucosa of a DR5/DR7 patient previously described 6 and highly reactive to the immunodominant gliadin peptide (DQ2.5-glia-α1,2, QLQPFPQPELPYPQPQP). DR5/DR7 B-LCL#23 (Table 1 ), carrying the DQ2.5 genes in trans configuration, displayed overlapping ability to stimulate cognate TCL with respect to DR1/DR3 B-LCL#5, as shown in dose curve response to DQ2.5-glia-α1,2 peptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…T cell lines (TCLs) highly reactive to wheat gliadin proteins were generated from jejunal biopsies of N = 3 HLA-DQ2.5 celiac patients, as previously reported ( 26 , 27 ). Briefly, mucosal cells were in vitro stimulated with an enzymatic (pepsin-chymotrypsin) digest of gliadin proteins (PC-gliadin) in complete medium (X-Vivo 15 medium supplemented with 5% AB-pooled human serum and antibiotics, all purchased by Lonza, Canberra Australia).…”
Section: Methodsmentioning
confidence: 99%
“…Potential‐CD is a condition defined by the presence of HLA DQ2/DQ8 risk alleles, positive CD‐associated serological markers but a mucosa with normal architecture . Recent findings have demonstrated the presence in the gut of subjects with potential‐CD of inflammatory T cells reactive to gluten peptides , concomitantly with the existence of regulatory mechanisms that counteract the activation of inflammatory pathways destructive of mucosal epithelium. Interestingly, another study has instead reported the lack of NK‐mediated cytotoxic pattern in the gut of this peculiar group of patients .…”
Section: Introductionmentioning
confidence: 99%